Retroperitoneal Abscess: A Case Series and Literature Review - Bahagianto, Aditya Fajar; Ismy, Jufriady (Universitas Aisyah Pringsewu, 2023)
Retroperitoneal abscess is one of the rare abscesses within the retroperitoneal space that has higher mortality and morbidity. The obscurity of exact clinical manifestations and diagnosis of the disease causes neglected inflammatory process which leads to worse progression. In this case series and literature review we describes four patients with retroperitoneal abscess. We report the clinical manifestation and treatment of retroperitoneal abscess. The patient often came with chief complaints of pain and feeling of fullness in the waist. CT scan usually revealed a hypodense lesion. The treatment consists of pharmacological treatment and surgical procedures. Nonspecific clinical manifestations often lead to misdiagnosis which causes the progression of disease. Early diagnosis and treatment is crucial for better outcome.